2018
DOI: 10.1007/s11999.0000000000000026
|View full text |Cite
|
Sign up to set email alerts
|

Can Dislocation of a Constrained Liner Be Salvaged With Dual-mobility Constructs in Revision THA?

Abstract: Level IV, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Neither study examined dualmobility implants, and their findings should be weighed against a large body of evidence that demonstrates relatively high rates of failure in constrained implants [13,15,28,29], acknowledging their utilization in patients of higher risk [8,9]. Recent reports of dualmobility implants in high-risk cohorts including abductordeficient patients suggest that they are effective in reduction of instability [12,22,30], consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Neither study examined dualmobility implants, and their findings should be weighed against a large body of evidence that demonstrates relatively high rates of failure in constrained implants [13,15,28,29], acknowledging their utilization in patients of higher risk [8,9]. Recent reports of dualmobility implants in high-risk cohorts including abductordeficient patients suggest that they are effective in reduction of instability [12,22,30], consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 73%
“…Instability remains a major concern after revision THA, and implant selection is one strategy to reduce the risk of further instability and failure [1,2,9,23,21,24]. Recent studies of dualmobility implants have demonstrated good outcomes in primary [25][26][27] and revision THA [20,22]. Notably, several studies have examined their use in high-risk cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozden et al [31] reported successfully treating instability with dual mobility in a series of 17 patients with abductor deficiency at the time of acetabular revision. Dual mobility has also been effective as a salvage procedure in patients who have failed a previous constrained liner [32]. The dual-mobility construct offered by the hip system that the authors typically use was not FDA approved until 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative dislocations are often associated with poor soft-tissue conditions and poor bone stock [28,29]. A recent study by Chalmers et al reported promising results, over a short-term follow-up period, with the implantation of dual mobility cups in revision procedures carried out due to recurrent dislocation [32].…”
Section: Discussionmentioning
confidence: 99%